On the road to the Wolf's Lair : German resistance to Hitler - Hamerow, Theodore S., 1920-2013 24.08.1920-16.02.2013 (Belknap Press, 1997)
The resisters in On the Road to the Wolf's Lair are not the singular souls doomed to failure by the massive Nazi machinery, but those who emerged from the Third Reich itself - those people whose cultural, administrative, and military positions allowed them, ultimately, to form a systematic, organized opposition to the Nazi regime. These were people with a vested interest in the Third Reich, and their slow and painful awakening to its evils makes a dramatic story, marked as much by temporizing and compromise, vacillation and reluctance - a resistance to conscience - as by the intrigue and heroics of political resistance that finally emerged. Hamerow follows these men as, one by one, they find themselves overwhelmed by guilt and contrition over their support of a murderous regime. He shows how their awakened moral reckonings and higher interests overrode lifetime habits and disciplines on the road to "the wolf's lair."